Concepts for Proposing a Classification System for Higher Education Institutions in Chile (GESTIÓN Y TENDENCIAS, 2024)
The author proposes a new taxonomy for classifying Chilean universities, criticizing the current scheme that divides institutions simply by ownership (state vs. private) as "too narrow" to reflect the diversity of the system. The central proposal argues that the allocation of state resources should be based not solely on an institution's legal nature, but on the type of goods it produces: public goods (non-excludable and non-rival) or private goods.The article applies economic analysis to university outputs: undergraduate teaching tends to be a private good (with exceptions in strategic or low-demand programs), whereas basic research and certain outreach activities are pure public goods. A three-dimensional model is proposed, cross-referencing: 1) ownership, 2) legal organization, and 3) the outputs offered. Under this model, a private non-profit university that generates public goods (such as open basic research) should receive state support for that specific function, just as a state university would. The author concludes by defining categories such as "comprehensive", "teaching", and "research" universities in order to allow an allocation of public resources
Keywords: higher education; public goods; state funding; university taxonomy; economics of education